CT Perfusion Dynamics of Intracranial Tuberculomas - Ravindra Bhimrao Kamble; Jayakumar Peruvumba N.; Ravishankar Shivashankar (Journal of Clinical and Diagnostic Research, 2015)
Aims: To study perfusion characteristics of intracranial tuberculomas and analyze changes with anti tubercular treatment. Materials and Methods: Nineteen patients of histologically proven intracranial tuberculomas were included in the study of which 9 were not on antitubercular treatment and ten were on antitubercular treatment (6 patients on treatment for less than 2 months and 4 were more than 6 months). All patients underwent CT perfusion (CTP) and CTP parameters like rCBV and rCBF were obtained from entire lesion, center and capsule of lesions and compared. Results: CTP parameters like rCBF and rCBV were significantly low in all the three ROIs in the group not on treatment compared to that of on treatment ; rCBF and rCBV of entire lesion (p=0.018 and p=0.005 respectively), capsule (p=0.045 and p=0.010 respectively) and center of the lesion (p=0.020 and p=0.009) respectively). Tuberculomas on antitubercular treatment of more than six months showed reduced rCBF and rCBV in entire lesion (p=0.01 & p=0.01 respectively), capsule (p=0.04 & p=0.03 respectively) and center (p=0.08 & p=0.05 respectively) compared to those on treatment for less than two months. Similarly tuberculomas on treatment for six months did not show significant difference in rCBF and rCBV compared to tuberculomas who were not on treatment. Tuberculomas on treatment for less than two months showed statistically increased rCBF and rCBV in entire lesion (p=0.01 & p=0.04 respectively), capsule (p=0.03 & p=0.01 respectively) and center (p= 0.03 &=0.01) compared to those not on treatment. Conclusion: Intracranial tuberculomas not on treatment and those on treatment for around six months show low perfusion and tuberculomas on treatment for less than two months show high perfusion. These findings suggest that serial perfusion profiles of tuberculomas on treatment could possibly be seen as surrogate markers of response to treatment.